Etiology of molar incisor hypomineralization – A systematic review. Issue 4 (28th April 2016) - Silva, Mihiri J.; Scurrah, Katrina J.; Craig, Jeffrey M.; Manton, David J.; Kilpatrick, Nicky
Abstract: Objectives: Molar incisor hypomineralization (MIH) is a common developmental dental defect of permanent teeth, which can increase the risk of dental caries, infection and hospitalization. The etiology is currently unclear although prenatal or early childhood health factors are suspected. The aim of this systematic review was to assess the strength of evidence linking etiological factors with MIH. Methods: A systematic search was conducted using the Medline and Embase electronic databases for studies investigating environmental etiological factors of MIH. Two reviewers assessed the eligibility of studies. The level of evidence and bias was determined for all eligible studies according to Australian National Health and Medical Research Council guidelines for systematic reviews of etiology and the Newcastle–Ottawa Scale. Results: From a total of 2254 studies identified through electronic and hand searching, 28 were eligible for inclusion. Twenty‐five of these investigated MIH and three investigated a related condition in primary teeth, hypomineralized second primary molars (HSPM), and these were analysed separately. A limited number of studies reported significant associations between MIH and pre‐ and perinatal factors such as maternal illness and medication use in pregnancy, prematurity and birth complications. Early childhood illness was implicated as an etiological factor in MIH in several studies, in particular fever, asthma and pneumonia. The studies investigating HSPM revealed an association with maternal alcohol consumption, infantile fever and ethnicity. However, the validity of these findings is impaired by study design, lack of adjustment for confounders, lack of detail and consistency of exposures investigated and poor reporting. Conclusions: Childhood illness is likely to be associated with MIH. Further prospective studies of the etiology of MIH/HSPM are needed.